The spatial distribution of Antarctic krill (Euphausia superba Dana) aggregations - Miller, Denzil George Maxwell (Department of Biological Sciences, 2024)
In nature, many biota exhibit recognisable spatial groupings, commonly termed "clumps" or "patches" (Hutchinson 1953; Diggle 1983; Wilson 1978). Attempts to devise measures of such aggregation are usually based on statistically determining the frequency distributions of selected organism parameters (Morisita 1959; Pielou 1977; Okubo 1980). In their field study of the spatial distribution of some 102 species (ranging from protozoa to humans), Taylor et al. (1979) concluded that such data were on average significantly more clumped than random. Since theoretically derived contagious distributions are often fitted to observed frequency distributions of this kind (Bliss 1971), the underlying spatial patterns are therefore usually concluded to be "patchy" (i.e. the organism is unevenly distributed in space). This, however, does not allow for concrete conclusions to be drawn about the underlying mechanism(s) inducing the observed distribution(s) and provides little more than sample statistics for, or at best a static picture of, the spatial pattern of the organism(s) concerned (Okubo 1980). Fmihermore, unless patches are essentially discrete their resulting distributions are often difficult to discern objectively (Skellam 1952; Waters and Henson 1959).